The effect of E-CRM on customer loyalty with customer satisfaction as a mediation variable: Study of users of BNI Direct South Sumatra - Kariman, Aulia; Wahab, Zakaria; Shihab, Muchsin Saggaff; Natalisa, Diah (International research journal of management, IT and social sciences, 2022)
This study aims to measure the effect of E-CRM on customer loyalty through customer satisfaction in 2021 by testing the variables of E-CRM, customer satisfaction, and customer loyalty using BNI Direct. The sample taken in this study amounted to 100 customers/debtors managed by BNI. Using PLS-SEM, the results show that the E-CRM variable contributes 58.7 % to BNI Direct customer satisfaction. This means that BNI Direct customer satisfaction can be explained through E-CRM activities carried out by BNI Direct. Furthermore, the variables of E-CRM and satisfaction contributed 67.6 % to BNI Direct customer loyalty substantially (powerfully). This means that BNI Direct customer loyalty can be explained through BNI Direct's E-CRM activities and the creation of customer satisfaction.